2017
DOI: 10.1016/j.dld.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir or tenofovir monotherapy prevents HBV recurrence in liver transplant recipients: A 5-year follow-up study after hepatitis B immunoglobulin withdrawal

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 0 publications
4
20
1
3
Order By: Relevance
“…However, the fact that there was an improvement in renal dysfunction in most patients following dose reduction of TDF suggests the drug played some role. This may also be supported by the fact that the cohort study by Manini et al suggested that lower rates of renal dysfunction on TDF and prespecified dose adjustments were utilized in their cohort but not in our cohort . The improvement in renal dysfunction following dose reduction of TDF is similar to a previous report on chronic hepatitis B by Fung et al, where 67% of renal dysfunction was reversed with dose adjustment of TDF .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the fact that there was an improvement in renal dysfunction in most patients following dose reduction of TDF suggests the drug played some role. This may also be supported by the fact that the cohort study by Manini et al suggested that lower rates of renal dysfunction on TDF and prespecified dose adjustments were utilized in their cohort but not in our cohort . The improvement in renal dysfunction following dose reduction of TDF is similar to a previous report on chronic hepatitis B by Fung et al, where 67% of renal dysfunction was reversed with dose adjustment of TDF .…”
Section: Discussionsupporting
confidence: 84%
“…It demonstrates the durable efficacy in preventing HBV recurrence and general tolerability of the TDF/LAM combination in the posttransplant setting. There has been a recent cohort study of 77 patients assessing the use of either TDF or entecavir monotherapy following HBIg withdrawal in hepatitis B‐infected individuals to prevent posttransplant recurrence, which had similarly low rates of recurrence of 9% over a median 6‐year follow‐up . This cohort had a greater proportion of Caucasians than our cohort, which primarily included people of Asian ethnicity, and our cohort was also older (median age 60 vs 53 years), with a longer period on HBIg (median 120 vs 60 months).…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, we analysed the risk of HBV recurrence post‐LT in 357 HBsAg‐positive patients after LT, 48 of whom had HBV recurrence during a median follow‐up of 36.6 months (range 0.4‐107.3 months). The rate of HBV recurrence in our study was higher than the recurrence rate reported by Western researchers, but comparable to the findings of Asia‐Pacific scholars . This discrepancy in recurrence rates may be due to the fact that most subjects are infected with genotype C in the Asia‐Pacific region, which is associated with a higher risk of resistant mutants .…”
Section: Discussionsupporting
confidence: 68%
“…Several studies have reported that the HBV DNA replication status pre‐LT is highly predictive of HBV recurrence, and a higher viral load at the time of LT is significantly associated with HBV recurrence rate post‐LT . However, other studies found no significant association between HBV DNA and post‐transplant recurrent HBV . In our study, the incidence of HBV recurrence was significantly different between patients with positive versus negative viral load based on Kaplan‐Meier analysis, the cumulative recurrence rates were 29.7% and 15.7%, respectively (Figure A), but which was not selected as independent risk factors for HBV recurrence using a multivariable Cox proportional hazards regression model with forward elimination, even using 5 log copies/mL as the cut‐off of DNA level.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation